2008
DOI: 10.1128/jcm.00818-07
|View full text |Cite
|
Sign up to set email alerts
|

Metallo-β-Lactamase Detection: Comparative Evaluation of Double-Disk Synergy versus Combined Disk Tests for IMP-, GIM-, SIM-, SPM-, or VIM-Producing Isolates

Abstract: The emergence of metallo-␤-lactamase (MBL)-producing isolates is a challenge to routine microbiology laboratories, since there are no standardized methods for detecting such isolates. The aim of this study was to evaluate the accuracy of different phenotypic methods to detect MBL production among Pseudomonas spp., Acinetobacter spp., and enterobacterial isolates, including GIM, IMP, SIM, SPM, and VIM variants. A total of 46 genetically unrelated Pseudomonas aeruginosa, Pseudomonas putida, Acinetobacter sp., an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
125
2
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(143 citation statements)
references
References 32 publications
4
125
2
12
Order By: Relevance
“…9 However, we can wonder how much longer these bacteria will persist susceptible to these remaining drugs if this selective pressure goes on. Comparing different phenotypic tests to detect MBL, we found that ceftazidime disk and mercaptopropionic acid association, in a double disk synergy test, was the most sensitive and specific assay, as it was reported by Picão et al 7 We observed that all other combinations of substrata and inhibitors (imipenem and mercaptopropionic acid; imipenem and mercaptoacetic acid; imipenem and EDTA; ceftazidime and mercaptoacetic acid; ceftazidime and EDTA) showed maximum specificities (100%), but low sensitivity to these combinations (zero to 71.4%), restricting their utilization. In spite of the high cost, MBL E-test strips can be employed to detect the MBL-producing P. aeruginosa due its high sensibility and specificity.…”
Section: Introductionsupporting
confidence: 69%
See 3 more Smart Citations
“…9 However, we can wonder how much longer these bacteria will persist susceptible to these remaining drugs if this selective pressure goes on. Comparing different phenotypic tests to detect MBL, we found that ceftazidime disk and mercaptopropionic acid association, in a double disk synergy test, was the most sensitive and specific assay, as it was reported by Picão et al 7 We observed that all other combinations of substrata and inhibitors (imipenem and mercaptopropionic acid; imipenem and mercaptoacetic acid; imipenem and EDTA; ceftazidime and mercaptoacetic acid; ceftazidime and EDTA) showed maximum specificities (100%), but low sensitivity to these combinations (zero to 71.4%), restricting their utilization. In spite of the high cost, MBL E-test strips can be employed to detect the MBL-producing P. aeruginosa due its high sensibility and specificity.…”
Section: Introductionsupporting
confidence: 69%
“…Colistin-only susceptible P. aeruginosa is a relatively contemporary issue, once carbapenems remained as effective therapeutic choice until the carbapenemases emergence on the last two decades. 7,8,14 Investigating MBL-encoding genes, we found isolates carrying bla SPM and bla IMP genes that together correspond to 29.8% of evaluated samples. In Brazil, the dissemination of P. aeruginosa carrying bla SPM gene has been reported throughout from several regions, 15,16 and SPM is the prevalent MBL among the isolates, although other enzymes have also been described, but with low frequency.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Detection of MBL producing isolates by PCR is expensive, requires specialized technicians and instruments, and more importantly, is able to detect only previously described MBL-encoding genes (Picão et al, 2008). The development of simple screening tests to detect acquired MBL production is a crucial step towards large scale monitoring of these emerging resistant determinants (Manoharan et al, 2010).…”
Section: Resultsmentioning
confidence: 99%